2012
DOI: 10.1089/hgtb.2011.231
|View full text |Cite
|
Sign up to set email alerts
|

A Capillary Electrophoresis Sequencing Method for the Identification of Mutations in the Inverted Terminal Repeats of Adeno-Associated Virus

Abstract: Inverted terminal repeat (ITR) integrity is critical for the replication, packaging, and transduction of recombinant adeno-associated virus (rAAV), a promising gene therapy vector. Because AAV ITRs possess 70% GC content and are palindromic, they are notoriously difficult to sequence. The purpose of this work was to develop a reliable ITR sequencing method. The ITRs of two molecular clones of AAV2, pTZAAV and pAV2, were (1) sequenced directly from plasmid DNA in the presence of denaturant (direct sequencing me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…S5 A and B). Since the high GC content of the palindromic AAV ITRs is known to be difficult to sequence through, we developed a method that keeps the ITRs sufficiently denatured so as to reproducibly obtain complete sequence reads (40). Sequence analysis from edited CD34 + , K562, and HepG2 cells revealed that targeted insertion was precise, with the chromosomal sequences being contiguous with HA sequences, followed by the SA/T2A and the GFP ORF.…”
mentioning
confidence: 99%
“…S5 A and B). Since the high GC content of the palindromic AAV ITRs is known to be difficult to sequence through, we developed a method that keeps the ITRs sufficiently denatured so as to reproducibly obtain complete sequence reads (40). Sequence analysis from edited CD34 + , K562, and HepG2 cells revealed that targeted insertion was precise, with the chromosomal sequences being contiguous with HA sequences, followed by the SA/T2A and the GFP ORF.…”
mentioning
confidence: 99%
“…This might be partly due to non-HDR integration of AAV donor with ITR (Inverted Terminal Repeat), whose secondary structure hampers PCR. However, we could not determine vector-derived sequences, even by PCR with 7-deaza-dGTP, which improves PCR for AAV-ITR (data not shown) ( Mroske et al., 2012 ). We could not rule out intra-vector deletion of concatemeric insertion either ( Nowrouzi et al., 2012 ).…”
Section: Resultsmentioning
confidence: 95%
“…Junctions of the circular AAV were amplified using two couples of primers surrounding the ITRs (online supplementary table 2) in 2.5% glycerol and 5% dimethyl sulfoxide. PCR products were sequenced by Sanger after ExoSAP-IT (Applied Biosystem) purification 41…”
Section: Methodsmentioning
confidence: 99%